2023
DOI: 10.1007/s12351-023-00745-1
|View full text |Cite
|
Sign up to set email alerts
|

ESG performance, herding behavior and stock market returns: evidence from Europe

Abstract: This paper tests how financial performance indicators and combined ESG score for large-cap stocks impact on stock return. In particular, we examine how market capitalization, price to book value, Sharpe ratio and ESG score of large-cap firms in Europe are related to their stock performance. We consider a panel data consisting of six European countries—Portugal, Italy, Greece, Spain, France and Germany—for the period 2010–2020. For Greek and French firms, a firm’s size tends to negatively affect its stock retur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…We use a more robust measure called Cross-Sectional Absolute Deviation (CSAD) presented by Chang et al . (2000) and Gavrilakis and Floros (2023).…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…We use a more robust measure called Cross-Sectional Absolute Deviation (CSAD) presented by Chang et al . (2000) and Gavrilakis and Floros (2023).…”
Section: Methodsmentioning
confidence: 98%
“…While investigating the herd behavior in Asian and European stock markets during the COVID-19 pandemic it is found that most of the European and UK market remained inefficient during the time of pandemic which resulted in market destabilization. A similar study conducted by Gavrilakis and Floros (2023) investigates the impact of herding behavior on stock returns in six selected European stock markets. In the recent literature of herding behavior, Spillover of herd anomaly has gained an increasing interest of researchers.…”
Section: Investigation Of Herding Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Herding tendency signi cantly impacts advisors' perspectives on ESG investments, a phenomenon empirically validated in studies conducted in Portugal, Italy, and Greece(Gavrilakis & Floros, 2023). (Garg, Goel, Sharma, & Rana, 2022) had previously posited that contingent upon the prevailing attitudes within their personal and professional networks, herding tendencies may either amplify or mitigate the positive or negative attitudes held by investors towards socially responsible investments.…”
mentioning
confidence: 89%
“…While herd behavior has been extensively studied in financial markets (Gavrilakis and Floros 2023;Bougatef and Nejah 2023;Fei and Zhang 2023;Yang and Chuang 2023;Tlili et al 2023;Bogdan et al 2022;Bouri et al 2021), its study in the cryptocurrency market is still limited. Therefore, this article focuses on herd behavior in the crypto market for several reasons.…”
Section: Introductionmentioning
confidence: 99%